Dinuclear metallocene complexes for high-performance supported catalysts - Bae, Sung Moon; Jeong, Sun Mi; Baek, Jun Won; Lee, Hyun Ju; Kim, Hagjun; Yoon, Yeokwon; Chung, Sangchul; Lee, Bun Yeoul (European Polymer Journal, 2021)
For application in commercial slurry and gas-phase processes, single-site homogeneous metallocene catalysts are typically immobilized on silica surfaces to control the size and morphology of the generated polymer particles. However, the main challenge limiting the commercialization of these catalysts is the enhancement of their productivity (measured in kg-PE/g-(supported catalyst)). Herein, we demonstrate that the productivity of supported catalysts can be enhanced by using dinuclear metallocene complexes instead of the conventional mononuclear analogs to prepare the supported catalysts. Thus, the productivity of the supported catalysts prepared by reacting methylaluminoxane (MAO)-treated silica (denoted as silica-MAO) with dinuclear ansa-metallocene complexes synthesized with silylene-bridged and thiophene-fused cyclopentadienyl ligands was almost twice that of the catalysts prepared with the mononuclear analogs. The enhanced productivity is because of the higher loading of the dinuclear complexes than that of the mononuclear analogs; the fed dinuclear complexes were entirely anchored on silica-MAO at 90–150 μmol-Zr/g-(silica-MAO) feed, whereas only a part of the fed mononuclear metallocene complexes was anchored on silica-MAO even at 90 μmol-Zr/g-(silica-MAO) feed. In addition, the supported catalysts prepared with the dinuclear complexes suppressed the formation of large polymer particles.
Keywords: Ansa-metallocene complexes; Cyclopentadienyl ligands; Dinuclear complex; Dinuclear metallocene complexes; Gas phase process; Metallocene catalyst; Metallocene complexes; Methylaluminoxane; Ethylene polymerization; Metallocene catalyst; Methylaluminoxane; Silica; Slurry process; Supported catalyst